PENGEMBANGAN MEDIA INTERAKTIF KLASIFIKASI MAHLUK HIDUP PADA SMP MUHAMMADIYAH 1 DENPASAR - Suryanti Kusuma, Aniek; Welda (Jurnal Penjaminan Mutu, 2024)
The learning process utilizes learning resources, especially learning media, so far at SMP Muhammadiyah 1 Denpasar in science learning, students only use teaching media in the form of textbooks and Student Worksheets (LKS) which are distributed by the school for students to own or buy. So far, science teachers, especially at SMP Muhammadiyah 1 Denpasar, have only been guided by the available textbooks or worksheets. The media used in delivering material during the teaching and learning process is still conventional in the form of whiteboards, textbooks, worksheets, PPT slides using a monotonous lecture method so that students feel bored. Based on the results of the questionnaire distributed to teachers and students, it is deemed necessary to develop interactive-based learning media, in order to make the learning atmosphere more varied. This research obtained 34 respondents at the start of the research from students at SMP Muhammadiyah 1 Denpasar by distributing online questionnaires. After obtaining the percentage calculation results, a conclusion can be drawn that 80% of students answered yes to the learning material for the classification of living things. This research aims to help students better understand the material on the classification of living things with interesting, effective and practical learning media. The method used in this research is the research and development (R&D) method, which uses the stages of the ADDIE access model. This Interactive Media will be tested by testing students' level of understanding, material testing and media expert testing. Keywords: Interactive Media, Classification of Living Things, ADDIE.